On the same page: collaborative research assignment design with graduate teaching assistants. Issue 3 (1st August 2019) - Murphy, Maggie
Abstract : Purpose: This paper aims to explore how collaborative research assignment design consultations between instruction librarians and new graduate teaching assistants (GTAs) have the potential to improve the design of research assignments for first-year writing courses. Design/methodology/approach: The author conducted a small number of questionnaires and structured interviews with first-time GTAs who serve as first-year composition instructors to explore their conceptions about teaching researched writing. Thematic analysis of the results of these qualitative instruments led to the design of a new framework for working with incoming cohorts of GTAs at her institution prior to the start of each fall semester. Findings: New GTAs often emphasize strict source type parameters in research assignment design and expect their students to engage in expert research behaviors. Emphasizing the assignment design expertise of instruction librarians during new GTA orientation may lead to more assignment design consultations with first-time college writing instructors. Collaborative assignment design consultations between librarians and GTAs can improve the alignment of research assignment parameters with their shared goals for students' research and writing skills and habits of mind, including seeing research and writing as iterative and inquiry-based processes. Research limitations/implications: While not every instruction librarian works with GTAs, working with instructors to collaboratively design research assignments that shift focus away from using specific search tools and locating particular types of sources opens possibilities for what librarians are able to achieve in one-shot instruction sessions, in terms of both lesson content and pedagogical strategies used. Originality/value: The existing literature on first-year writing addressing faculty and librarian assignment design collaborations, and research assignments more generally, does not often explicitly examine the experiences of librarians who primarily work with GTAs. This paper adds to this literature by highlighting specific obstacles and unique opportunities in librarian–GTA teaching partnerships in first-year writing courses.